Sprinkling of holy water on the bullock carts - Mumbai Archive Project Team (Jio Institute, 2024)
Father Oscar Mendonca sprinkles holy water on the carts upon their arrival at the church. The holy water sprinkler used in Christian liturgy is called an aspergillum or aspergil.